Social Services First Five Year Plan an Appraisal Directorate of Economics and Statistics Government of Rajasthan - Planning Commission (Planning Commission, 1949)
The State of Rajasthan was constituted during 1949 by the merger of erstwhile twenty-two Princely States, whose economy was directed largely towards ensuring comforts to the landed aristocracy and the like, and very few amenities were provided for the public in general. However, the later decades of the first half of the present century witnessed some feverish activity in some of the States to provide some of the primary Social Services viz., Education, Medical and Public Health, Labour Welfare, Housing and others, for the harmonious development of physical and mental capacities of the people.
Directorate of Economics and Statistics Government of Rajasthan